Traugutta róg Mierniczej. Małomiasteczkowość nieopodal centrum europejskiego miasta średniej wielkości w pierwszej połowie lat 60. XX wieku - Pułka, Leszek (2023)
The article is an anthropological reconstruction of the microcosm of the Wrocław district called the Bermuda Triangle in the first half of the 1960s. The author describes a specifically small-town community and its space-time identity, largely free from the oppressive media practices of global culture remaining in the shadow of the Catholic type of religiosity. The culture of the Triangle at that time turned out to be a collection of urbanized behaviours as well as a type of slightly archaic, face-to-face private-public discourse, marking the coexistence of original communications placed in the collective field of view and preserved in collective memory. The basic principle organizing the notes of an anthropologist of the (photo)past is the analysis of relics and artefacts.
Keywords: Wrocław; small-town character; cultural identity; local culture of the 1960s; narratives; lifestyles